Pengembangan LKPD Fisika Kelas X Berbasis DBL (Discovery Based Learning) Dilengkapi Soal HOTS - Artha Nesa Chandra; Miftahul Hayati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The absence of physics teaching materials developed for students that involves activities, searching for and finding concepts in accordance with learning objectives, coupled with the low HOTS ability of students in analyzing questions is a reality in the field that underlies this research. So that researchers are interested in developing a physics worksheet based on DBL (Discovery Based Learning) equipped with HOTS questions. This study aims to produce DBL-based physics worksheets equipped with valid and practical HOTS questions for work and energy, momentum and impulse and harmonic vibrations. Research and Development with a 4-D model is a type of research developed. The stages of this research consist of 4 phases, namely Definition, Design, Development and Dissemination. However, due to time and cost constraints, this research was only carried out until the development stage. DBL-based physics worksheets equipped with HOTS questions are designed with six learning stages, namely Stimulation, Problem Statement, Data Collection, Data Processing, Verification and Generalization. Based on the data analysis that has been done, the results of the validation of the DBL-based physics LKPD are equipped with HOTS questions with a percentage of 78.33% and valid categories. While the results of the practicality questionnaire responses of teachers and students were obtained respectively 85.54% and 91.18% with very practical criteria. So it can be concluded that the DBL-based physics worksheet development is equipped with valid and very practical HOTS questions to be used for class X high school students.